Pengaruh Pelatihan Dan Pendidikan, Pengalaman Kerja Personal Dan Partisipasi Manajemen Terhadap Efektivitas Penggunaan Sistem Informasi Akuntansi - Luh Putu Gita Sukmayanthi; I Wayan Sudiana; Ni Wayan Yuniasih (UNHI Press, 2023)
ABSTRACT In this study, the causal factors that can affect the Effectiveness of the Use of Accounting Information Systems in Savings and Loan Cooperatives in West Denpasar District will be analyzed. Some of the factors studied were Training and Education, Personal Work Experience, and Management Participation. In this study, all employees of the Savings and Loans Cooperative in West Denpasar District were used as the research population in which the sample amounted to 78 people. The data in this study will be analyzed using multiple linear regression analysis techniques. The results of the study indicate that the existence of training and education programs, personal work experience, and management participation will be more effective in the use of accounting information systems in producing information. Keywords: Effective Use of Accounting Information Systems Keywords: Effective Use of Accounting Information Systems